Sustainability of sharia rural bank in Central Java - Rosida Dwi Ayuningtyas; Rosita Wati; Fitroh Safa’ah (Jurnal Ekonomi & Keuangan Islam, 2018)
This study analyzes the sustainability of the Islamic people's financing bank (BPRS) in Central Java in the period 2013 to 2017. The variables used in this study are financial sustainability ratio (FSR), non-performing financing, return on assets, financing debt ratio, operating expenses and capaital adequacy ratio. The sample selected in this study is 10 BPRS where the sample has published financial reports in Indonesian banks in 2013 to 2017. The analysis method used is panel data regression with the fixed effect method. In the test results that CAR partially has a positive effect on the financial sustainability ratio, while OER partially negatively affects the financial sustainability ratio. Based on the test results, BRPS Mount Slamet has the highest FSR value of 3.32%, while the lowest FSR is BPRS Saka Dana Mulia of 2.36%.